Fighting Discrimination Against Women: The Spirit of Muslim Feminism in Ki Hadjar Dewantara's Madjallah Wasita [1889-1959] - M. Nurdin Zuhdi (Brajamusti Publication, 2025)
This study is significant for understanding Ki Hadjar Dewantara's (KHD) contribution to the fight for women's rights, particularly through his writings in Wasita magazines (1928-1935). During this period, public awareness of women's rights was limited, and patriarchal traditions were deeply rooted in Indonesian society. The focus of this study is to analyze KHD's thoughts on women, as reflected in Wasita, and their impact on the development of women's thought in Indonesia. The research method employed a qualitative approach, analyzing texts published in Wasita magazines. The results show that KHD emphasized three main points: first, the importance of returning women to their natural role as mothers, which is considered as the foundation for maintaining moral values ​​and customs. Second, higher education for women is the key to national progress. Third, women's right to participate in the public domains, including obtaining decent work, while still observing norms of decency and security. KHD's thoughts in Wasita demonstrate an understanding far ahead of his time and are a valuable contribution to the fight for equal rights between women and men in Indonesia